Perspektif Mahasiswa Mengenai Kewajiban dan Hak Negara dan Warga Negara - Oktavia Marchelina Sukma; Aulia Armisyah Esra; Mutiara Fitri Santika; Olivia Andrea Br Bukit; Sri Yunita (Publikasi Indonesia, 2022)
This research aims to know the perspective of the students on the rights and obligations, and what are the rights and obligations of states and citizens, and to what extent the students understand about the rights and obligations of the state and citizens. Rights and obligations are inherent in each individual and group. The study was done through distribution of the angkets (questionnaires). The method employed in this study is a qualitative descriptive method. This understanding of rights and obligations is surely essential to living in a prosperous, comfortable, and secure country.